2019
DOI: 10.1007/s00167-019-05352-2
|View full text |Cite
|
Sign up to set email alerts
|

Morphological structure and variations of fetal lateral meniscus: the significance in convenient diagnosis and treatment

Abstract: Purpose The aim of this study is to evaluate of morphometry of the lateral meniscus (LM) and determine incidence of the LM shapes. Methods This study was performed on fetal cadaver collection of Anatomy Department of Necmettin Erbakan University. Fifty human fetal cadavers (25 female, 25 male human fetal cadavers) were used in this study. Microdissection was performed. Morphometric measurements were performed. LM were classiied into four types and ive subtypes. ResultsIn this study, it was identiied that all p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 36 publications
0
12
0
Order By: Relevance
“…Some demographic reports have pointed that DM's prevalence related to race factor, and it usually occurs in Asian and Hispanic 13,20 . In microstructure and histology study, many researches illuminated that DM's bril collagen is different with normal meniscus, which mainly re ect on the quantity and arrangement [5][6][7][8][9][10][11] . Based on clinical reports, discoid lateral meniscus (DLM) have higher incidence that approximate 0.4% to 17% than discoid medial meniscus (DMM) approximated 0.06% to 0.3% 21 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some demographic reports have pointed that DM's prevalence related to race factor, and it usually occurs in Asian and Hispanic 13,20 . In microstructure and histology study, many researches illuminated that DM's bril collagen is different with normal meniscus, which mainly re ect on the quantity and arrangement [5][6][7][8][9][10][11] . Based on clinical reports, discoid lateral meniscus (DLM) have higher incidence that approximate 0.4% to 17% than discoid medial meniscus (DMM) approximated 0.06% to 0.3% 21 .…”
Section: Discussionmentioning
confidence: 99%
“…DM is not only a kind of morphology variant also a microarchitecture variant. [5][6][7][8][9][10][11] Meanwhile, familial case report about DM implied that it may be related to genetic diease. 12 A newly demographics and epidemics researches pointed that DM appears different prevalence in different race.…”
Section: Introductionmentioning
confidence: 99%
“…7,[38][39][40][41] Morphologically, DLM is broader, the coverage area of the lateral tibial plateau is more than 70%, and the incidence of peripheral rim instability is higher (38%-88%). 1,3,9,[42][43][44] Histologically, the circular collagen fiber of DLM is sparse and disordered in arrangement, and the proportion and distribution of cells differ from NLM 3,[10][11][12][13][14][15][16] (Grade E).…”
Section: Agree 36/36 100%mentioning
confidence: 99%
“…Clinically, DLM is often accompanied by potential peripheral rim instability, dysplasia of lateral femoral condyles, and abnormal lower limb axial alignment. 1,3,[9][10][11][12][13][14][15][16][17][18][19][20][21] These pathophysiological features of DLM enable it to be prone to degeneration, lesions, and retear after arthroscopic surgery, usually presenting as symptoms such as pain, swelling, snapping, locking, giving way, or limited motion. [22][23][24] As the condition progresses, it often combines with articular cartilage lesions or degeneration, and knee osteoarthritis will occur.…”
Section: Introductionmentioning
confidence: 99%
“…31 32 The precise aetiology of a discoid meniscus is unknown, although some authors suggested that it is congenital, with a genetic or familiar predisposition for the development of discoid menisci. 14 33 34 According to Aydın Kabakçı et al 35 on human fetal cadavers, a fetal lateral meniscus classification was described, leading to a better understanding of the morphological development of fetal meniscal development.…”
Section: State Of the Art Review Embryology And Anatomymentioning
confidence: 99%